Lumbar alignment: its role on plantar pressure and postural sway in people with low back pain - Harem Abdalqadir Mohammed; Ali Yalfani; Dara Latif Saifalddin; Saiwan Sirwan Mohammed; Hiwa Ahmed Rahim (spdfharmony.com, 2025)
Background: Low back pain (LBP) is a global health concern influenced by biomechanical factors, including lumbar alignment. Altered lumbar curvature (hyperlordosis/hypolordosis) may disrupt posture, plantar pressure distribution, and postural stability, contributing to LBP pathophysiology. Aim: This study investigated the impact of lumbar alignment on plantar pressure patterns and postural sway in individuals with LBP. Methods: Thirty-six participants (18–25 years) were categorized into hyperlordosis, hypolordosis, and normal lordosis groups. Lumbar curvature was measured using a flexible ruler, while plantar pressure and center of pressure (COP) parameters were assessed via the Zebris FDM-S platform during bipedal and unipedal standing. Statistical analysis included ANOVA and Tukey’s post hoc tests (SPSS v26, p<0.05). Results: The normal lordosis group exhibited significantly smaller COP confidence ellipse parameters (minor/major axis length, area) and lower postural sway compared to hyperlordosis and hypolordosis groups (p<0.05). Anterior-posterior plantar pressure asymmetry was pronounced in hyperlordosis (anterior shift) and hypolordosis (posterior shift). No significant differences were observed in mediolateral COP displacement or bilateral foot symmetry (p>0.05). Conclusion: Normal lumbar alignment enhances postural stability and balanced plantar pressure distribution, whereas hyperlordosis and hypolordosis correlate with increased postural fluctuations and asymmetric foot loading. Rehabilitation strategies targeting lumbar alignment may improve biomechanical outcomes in LBP management.